Perfil de resistência a antimicrobianos de bactérias isoladas de amostras de águas das escolas estaduais de Boa Vista - RR - Pessoa, Ilzo Costa (2011)
One of the main concerns of humanity nowadays is water: its availability and its quality. An inadequate exploitation of the sources results in the contamination of both superficial and deep waters, which become a public health hazard. Bacteria are one of these biological sources of water contamination, responsible for countless diseases which are treated with antimicrobials. The widely spread use of antimicrobials in human medicine along with animal production had resulted in a steady increase in the number of pathogenic and commensal bacteria resistant to antimicrobial agents, which in recent years are becoming one of the main problems of public health. This paper is a result of an interest in studying the quality of water consumed by the students of 20 state schools of the public school system of Boa Vista – RR, as well as trying to obtain a profile of antimicrobial resistance of the bacteria isolated in different water samples collected at these schools. Between October 2010 and April 2011, 40 water samples were collected from taps in lunchrooms, along with 40 samples from drinking wells, and all of them were submitted to microbiological examination. Using the multiple tubes technique, with 3 dilutions and a series of 5 tubes, we determined the total number of coliforms and thermotolerant coliforms. In agreement with the rules of the Standard Methods for the Examination of Water and Wastewater, the “pour plate” method was used at the CBio – UFRR to detect heterotrophic bacteria. Isolation and identification of microorganisms was done at LACEN – RR, using the biochemical series. In evaluating the resistance to antimicrobials, disk diffusion methods were used, in agreement with the established rules of the CLSI. In water samples that receive full treatment, 10% tested positive for total coliforms and, in chlorinated water samples, 20% tested positive for total coliforms and 2,5% for thermo-tolerant coliforms, which makes them inadequate for human consume. The counting of heterotrophic bacteria went from 1,4 x 10 to 3,6 x 10² CFU/mL of water, not surpassing what is established in the ordinance 518/2004/MS. The following Gram-negative bacteria (66,7%) were identified: Acinetobacter spp., C. violacea, Cocobacilos spp., E. aerogenes, E. coli, K. ozaenae, Leptothrix ssp. and Gram-negative glucose non fermenting bacillus. The Gram-positive bacteria identified were: B. subtilis, Micrococcus spp., S. aureus and Staphylococcus spp. The results of antibiotic sensibility tests revealed that most of the isolated bacteria were resistant to ampicilin (68,2%), 22,3% showed resistance to oxacilin and 22,7% were resistant to both eritromicin and meropenem. In Gram-positive bacteria, the growths of S. aureus isolated from water samples showed the greatest MAR index (0,61), while E. coli growths were the ones who showed the greatest MAR index in Gram-negative bacteria (also 6,1%). Results prove a great instability in the quality of water provided to the Boa Vista - RR population, being in its treatment, distribution or containment, as well as showing the presence of bacteria resistant to multiple antibiotics, which is a health hazard to the public.